Pengaruh Marketing Mix, Kualitas Pelayanan dan Citra Merk terhadap Keputusan Pembelian Produk Piston - Murdiono; Syariefful Ikhwan; Muhammad Syaifulloh; Roby Setiadi; Roni (Journal of Economics and Management (JECMA), 2019)
This study aims to determine and analyze the influence of marketing mix, quality of branding and brand image on the purchasing decision of fim piston on CV Takkara Auto Part Brebes in 2017-2018. This type of research is comparative causal research. This study used primary data and this research method used a questionnaire with a sample of 80 respondents. Hypothesis testing using multiple linear regression analysis. The results of this study partially influenced the marketing mix significantly on purchasing decisions, with a calculated t value of 14,180 > t table of 1,992 and a significance value of 0.000 < 0.05. Service quality has a significant positive effect on purchasing decisions, with a calculated t value of 6.482 > t table of 1.992 and a significance value of 0.000<0.05. And the brand image has a significant positive effect on purchasing decisions, with a calculated t value of -6.187 > t table of -1.992 and a significance value of 0.001 < 0.05. Simultaneously marketing mix, service quality and brand image have a significant effect on purchasing decisions, with a calculated F value of 375,591 > F of 2.725 and a significance value of 0.000 < 0.05.